The nexus between governance and the economic impact of whale-watching. The case of the coastal lagoons in the El Vizcaíno Biosphere Reserve, Baja California, Mexico. (1st August 2018) - Mayer, Marius; Brenner, Ludger; Schauss, Bernadette; Stadler, Claudia; Arnegger, Julius; Job, Hubert
Abstract: Whale-watching (WW) has gained considerable importance for coastal communities as a potentially sustainable form of marine resource use. However, as a common-pool resource, marine wildlife runs the risk of being overexploited, which can lead to negative effects on both animal populations and economic sustainability. Therefore, careful management and use regulation by capable institutions are required. But any governance arrangements that seek to comply with these exigencies need to be accepted by both (local) stakeholders and resource users. To assure compliance with regulations, the former must be involved in decision-making about management issues and should also partake in the economic benefits of WW. These two factors are major drivers of positive attitudes towards conservation governance. This article analyzes the nexus between governance and the economic impact of WW in the case of the coastal lagoons in the El Vizcaíno Biosphere Reserve (EVBR), Baja California, Mexico, a globally-renowned WW destination. The results of our research show that a government-led WW governance arrangement evolved over time in the EVBR to prevent overexploitation and restrict resource use by non-local operators, thus ensuring that mainly local service providers will profit from WW. Moreover, the Reserve's advisory board serves as a relatively effective negotiating platform that offers possibilities for participation by local stakeholders while also mitigating conflicts among actors that represent unequal powers. Therefore, these institutional arrangements are widely-accepted and supported by local actors who often rely on economic rationalism in their arguments. We calculated the economic impact of WW using an input-output model: ∼18, 000 whale-watchers produce an annual regional economic impact of US-$0.7 million and generate 334 seasonal and 180 year-round jobs. The opportunity costs related to restrictions on resource use are adequately compensated, so the case of WW in the EVBR supports the general feasibility of the people-oriented protected area approach and the suitability of biosphere reserves as governing institutions for marine wildlife tourism. Graphical abstract: Evolution of whale-watching-related regulations and local participation in El Vizcaíno Biosphere Reserve, Mexico. Image 1 Highlights: We analyze the nexus between whale-watching governance and economic impact by combining quantitative and qualitative surveys in Baja California Sur, Mexico. Management of common-pool resources requires efficient conflict mitigating and broadly accepted governmental institutions. Whale-watching generates US-$0.7 million regional income and 334 seasonal and 180 year-round jobs. Economic benefits are precondition for the acceptance of governance regimes. Protected areas are suitable for the governance of marine wildlife tourism.